SLEIGHT IS RIGHT: CYBER CONTROL AS A NEW BATTLEGROUND FOR AFRICAN ELECTIONS. - Amoah, Michael (African Affairs, 2020)
Sleight of hand in manipulating the computation of results has become the new might for deciding who wins presidential elections. It appears that whoever controls the computation exercises a right to take advantage and win, and whoever loses or relinquishes control of the computation loses the election. As incumbents do not want to be identified with direct interference or rigging, hacking has become an alternative means. This raises a serious challenge for election management bodies (EMBs) and a new frontier for international observation. As electronic data management has become a key battleground, international observers cannot restrict their monitoring to the manual process alone. However, individual states may have data sensitivity concerns about granting electronic monitoring access to partisan international observers. Institutionalizing internationally agreed protocols that would allow real-time monitoring of EMBs' computer systems by international observers or forensic audits of any stage of the electoral process to investigate interference, manipulation, hacking, and counter claims, is now a necessity. At the same time, the extent to which international monitors can be trusted to be non-partisan is of equal importance and could reduce forum shopping over time.